2004
DOI: 10.1039/b307194d
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid-promoted cyclization of heteroatom-substituted enynes

Abstract: Lewis acid-promoted cyclizations of heteroatom-substituted enynes have been examined. The reaction of enynes and bearing silicon substituents on an alkyne afforded the halogenated five-membered gamma-lactones and gamma-lactams as the main products. The reaction of substrates and having 2-phosphonoacrylate instead of malonate also gave halogenated five-membered cyclic compounds and as the major products. The cyclized products are highly substituted and potentially useful for further synthetic transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Thus, after investigation of a variety of Lewis acids, we found that FeCl 3 itself was also able to catalyze skeletal rearrangements of enynes (Table 8). This is in contrast with the cyclization of certain enynes promoted by stoichiometric amounts of FeCl 3 , which resulted in cyclization with concomitant addition of chloride to the triple bond 34. On the other hand, treatment of enyne 1 with the Fe 0 complex [Fe(CO) 4 (acetone)] had been reported to give Alder–ene cycloisomerization 35.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, after investigation of a variety of Lewis acids, we found that FeCl 3 itself was also able to catalyze skeletal rearrangements of enynes (Table 8). This is in contrast with the cyclization of certain enynes promoted by stoichiometric amounts of FeCl 3 , which resulted in cyclization with concomitant addition of chloride to the triple bond 34. On the other hand, treatment of enyne 1 with the Fe 0 complex [Fe(CO) 4 (acetone)] had been reported to give Alder–ene cycloisomerization 35.…”
Section: Resultsmentioning
confidence: 91%
“…Based on the results of some iron-catalyzed cross-coupling reactions, Fürstner et al were the first research group to propose a catalytic version of the cycloisomerization of enynes. [187][188][189] The low-valent iron complex [Li(tmeda)][CpFe(C 2 H 4 ) 2 ], readily prepared and isolated from inexpensive ferrocene, was found to be extraordinarily active for enyne rearrangements. The weakly ligated ethylene ligands can be readily substituted by an enyne moiety-in a similar way as for previously presented Pd-catalyzed reactions-and lead to an oxidative addition to give a cycloferrate complex.…”
Section: Fe-catalyzed Cycloisomerizationsmentioning
confidence: 99%
“…29 Allenes have also been isolated and characterized from many natural products, and over 150 compounds comprising this functionality in their structure are known. 30 The very few examples that report the preparation of allenes from enynes involve the use of a Lewis catalyst 31 or allenyl radicals. 32 To the best of our knowledge, only two allene compounds formed by the thermal intramolecular ene reaction of enynes have been previously reported, and their synthesis involves the use of a high temperature (210 °C) to achieve a moderate yield in one case, 33 and the formation of a nonisolable allene intermediate in the other.…”
Section: Thermally Induced Intramolecular Ene Reaction Of Fuller-16-enynes: Synthesis Of Fulleroallenesmentioning
confidence: 99%